CZecking heart failure in patients with advanced chronic kidney disease (Czech HF-CKD): Study protocol - Malik, Jan; Valerianova, Anna; Pesickova, Satu Sinikka; Hruskova, Zdenka; Bednarova, Vladimira; Michalek, Pavel; Polakovic, Vladimir; Tesar, Vladimir (The journal of vascular access, 2024)
BACKGROUND: Heart failure (HF) is a frequent cause of morbidity and mortality of end-stage kidney disease (ESKD) patients on hemodialysis. It is not easy to distinguish HF from water overload. The traditional HF definition has low sensitivity and specificity in this population. Moreover, many patients on hemodialysis have exercise limitations unrelated to HF. Therefore, we postulated two new HF definitions ((1) Modified definition of the Acute Dialysis Quality Improvement working group; (2) Hemodynamic definition based on the calculation of the effective cardiac output). We hypothesize that the newer definitions will better identify patients with higher number of endpoints and with more advanced structural heart disease. METHODS: Cohort, observational, longitudinal study with recording predefined endpoints. Patients (n = 300) treated by hemodialysis in six collaborating centers will be examined centrally in a tertiary cardiovascular center every 6-12 months lifelong or till kidney transplantation by detailed expert echocardiography with the calculation of cardiac output, arteriovenous dialysis fistula flow volume calculation, bio-impedance, and basic laboratory analysis including NTproBNP. Effective cardiac output will be measured as the difference between measured total cardiac output and arteriovenous fistula flow volume and systemic vascular resistance will be also assessed non-invasively. In case of water overload during examination, dry weight adjustment will be recommended, and the patient invited for another examination within 6 weeks. A composite major endpoint will consist of (1) Cardiovascular death; (2) HF worsening/new diagnosis of; (3) Non-fatal myocardial infarction or stroke. The two newer HF definitions will be compared with the traditional one in terms of time to major endpoint analysis. DISCUSSION: This trial will differ from others by: (1) detailed repeated hemodynamic assessment including arteriovenous access flow and (2) by careful assessment of adequate hydration to avoid confusion between HF and water overload.
Keywords: Renal Dialysis; Kidney Failure, Chronic; Water; Observational Studies as Topic; pozorovací studie jako téma; chronické selhání ledvin; longitudinální studie; dialýza ledvin; Česká republika; lidé; srdeční selhání; Humans; chronická renální insuficience; Heart Failure; Longitudinal Studies; Renal Insufficiency, Chronic; voda; Czech Republic